P15 Lacosamide monitoring in the serum of children with refractory epilepsy. Issue 6 (17th May 2019) - Kronenfeld, N; Kohn, E; Lezinger, M; Brandriss, N; Heyman, E; Bar-Chaim, A; Berkovitch, M
Abstract : Background: Lacosamide is indicated for various types of refractory epilepsy and as adjunctive therapy to other antiepileptic medications. Data on monitoring serum levels of lacosamide in pediatric patients is scarce. Objective: To evaluate the correlation between serum levels of lacosamide and the tolerability in children with refractory epilepsy. Methods: The medical records of 22 children with refractory epilepsy treated with lacosamide at Assaf Harofeh Medical Center were reviewed. Trough serum levels of lacosamide was measured using HPLC and correlated with its efficacy and safety. Results: Mean age of the children was 11 ± 4 (3–18) years. Median lacosamide daily dose was 9.3 (6.6–11) mg/kg and median plasma concentration was 7.1 (5.9–11.9) ug/ml. The therapeutic range of lacosamide serum concentration is 10 to 20 ug/ml. No change in seizures frequency was reported in 21.4% of children with lacosamide concentrations below 10 ug/ml. However, in 40% of the children, reduction of the seizures frequency was reported when serum concentration was above 10 ug/ml. No serious adverse events were reported during therapy. The prospective part of the study was initiated, and the first patients were recruited. Conclusion: Large studies, preferably prospective, on lacosamide serum monitoring including information on correlation with efficacy and safety are warranted. Disclosure(s): Nothing to disclose